BRICS Expansion: Decoding the Parody Play - Paul, Anurag (Jurnal Perpajakan dan Keuangan Publik, 2025)
This study presents a critical analysis of the BRICS expansion, particularly with the inclusion of geopolitically uneasy members such as Ethiopia, Egypt, Saudi Arabia, the UAE, and Iran. It hypothesizes that this transformation in membership composition serves as a façade—masking the bloc’s true strategic objectives behind a discourse of global inclusivity and multipolarity. Employing a mixed-methods approach, the research combines an extensive literature review with a comparative analysis between BRICS and traditional Western-dominated institutions. This method reveals BRICS’ unique strategies, particularly its use of mimicry and institutional rhetoric, which enable it to navigate and subtly challenge the dominant global order. The central question addressed is whether BRICS’ expansion enhances its capacity to act as a genuine alternative in global development governance or undermines its effectiveness as a counterbalance to the prevailing Western hegemony. The findings offer new insights into BRICS' identity, coherence, and strategic trajectory within the evolving landscape of international relations.